2001
DOI: 10.1038/35099520
|View full text |Cite|
|
Sign up to set email alerts
|

Self-assembled monolayer organic field-effect transistors

Abstract: The use of individual molecules as functional electronic devices was proposed in 1974 (ref. 1). Since then, advances in the field of nanotechnology have led to the fabrication of various molecule devices and devices based on monolayer arrays of molecules. Single molecule devices are expected to have interesting electronic properties, but devices based on an array of molecules are easier to fabricate and could potentially be more reliable. However, most of the previous work on array-based devices focused on two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(127 citation statements)
references
References 27 publications
2
119
3
Order By: Relevance
“…1 Some molecules can operate as diodes, 2 Coulomb blockade structures, 3 or switching devices with high negative differential resistance at room temperature. 4,5 Transistorlike behavior in molecular three-terminal devices ͑molecular transistors͒ has been demonstrated in a single C 60 fullerene connected to gold electrodes, 6 in organic self-assembled monolayers, 7 and in single-and multiwalled carbon nanotubes. 8,9 The source-drain current in these systems ͑three-terminal devices͒ is controlled by a gate voltage.…”
mentioning
confidence: 99%
“…1 Some molecules can operate as diodes, 2 Coulomb blockade structures, 3 or switching devices with high negative differential resistance at room temperature. 4,5 Transistorlike behavior in molecular three-terminal devices ͑molecular transistors͒ has been demonstrated in a single C 60 fullerene connected to gold electrodes, 6 in organic self-assembled monolayers, 7 and in single-and multiwalled carbon nanotubes. 8,9 The source-drain current in these systems ͑three-terminal devices͒ is controlled by a gate voltage.…”
mentioning
confidence: 99%
“…This is an issue that clearly needs a lot more attention, since the precise location of E F depends on the model for the contacts, as well as the method of calculating the molecular Hamiltonian. A third terminal (gate) [8] can help resolve some of these issues. One of the consequences of a self-consistent evaluation of energy levels is that as we raise the fermi energy, the levels float up by an amount equal to the charging energy (for a solid, this is roughly given by the capacitance of a sphere of radius equal to the size of the electronic wave function).…”
mentioning
confidence: 99%
“…Lopinski et al [11] have demonstrated the self-assembly of molecular silicon structures. And, most recently, Bell Labs has announced the construction, by selfassembly, of the world's first molecular-thickness transistor [19].…”
Section: Summary Of Recent Experimental Activitymentioning
confidence: 99%